Spolnost in spolno zdravje - Skoberne, Mihaela (Obzornik zdravstvene nege, 2004)
The article describes sexual health in the frames of ther dimensions of health, presents the definition of sexual health by WHO, and stressed the needthat sexuality is dealt with in the frames of nursing care as an integral part of an individual's well-being.
Keywords: Diabetes Mellitus; Duševne motnje; Hipertenzija; Hypertension; Mental Disorders; Miokardni infarkt; Myocardial Infarction; Negovalna diagnoza; Nursing; Nursing Diagnosis; Parafilije; Paraphilias; Sex Behavior; Sex Disorders; Sex Education; Sex Offenses; sexual intercourse; Sexuality; Sladkorna bolezen; Spolna vzgoja; Spolne motnje; Spolni prestopki; Spolno vedenje; Spolnost; Substance Abuse; Transseksualizem; Transsexualism; zdravje; zdravstvena vzgoja